2016
DOI: 10.1016/j.neuron.2016.11.037
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Terminal Effector Genes in Mammalian Neurons Is Maintained by a Dynamic Relay of Transient Enhancers

Abstract: SUMMARY Generic spinal motor neuron identity is established by cooperative binding of programming transcription factors (TFs), Isl1 and Lhx3, to motor-neuron-specific enhancers. How expression of effector genes is maintained following downregulation of programming TFs in maturing neurons remains unknown. High-resolution exonuclease (ChIP-exo) mapping revealed that the majority of enhancers established by programming TFs are rapidly deactivated following Lhx3 downregulation in stem-cell-derived hypaxial motor n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
69
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(77 citation statements)
references
References 49 publications
6
69
2
Order By: Relevance
“…In addition, our data show a combination of NKX2-1 and LHX6 binding to aREs that have an enrichment of E-box motifs. This combination of TFs (HD, LIM and E-box binding) is consistent with the transcriptional program governing the development and establishment of terminal effector gene expression in motor neurons [8,9]. These beautiful studies show that TFs are shuttled between different REs along the progression of motor neuron development.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…In addition, our data show a combination of NKX2-1 and LHX6 binding to aREs that have an enrichment of E-box motifs. This combination of TFs (HD, LIM and E-box binding) is consistent with the transcriptional program governing the development and establishment of terminal effector gene expression in motor neurons [8,9]. These beautiful studies show that TFs are shuttled between different REs along the progression of motor neuron development.…”
Section: Discussionsupporting
confidence: 71%
“…Distantly acting REs have been identified based on conservation and activity [3,4]. Their spatial activity and dynamic genomic contacts can be predicted using a combination of TF binding profiling, genomewide 3D chromosome organization mapping and CRISPR/Cas9 editing [5][6][7][8][9][10] Mouse genetic experiments have elucidated the functions of many TFs in the development of the subpallial telencephalon [11,12]. These studies show that the HD protein NKX2-1 is required for regional specification of the MGE by repressing alternative identities, as well as promoting GABAergic and cholinergic cell fates via the induction of TFs such as LHX6 and LHX8 [13][14][15][16][17].…”
Section: Resultsmentioning
confidence: 99%
“…Both iPSC reprogramming and normal development are thought to proceed through stepwise and gradual transitions, where prior steps bookmark enhancers for activation in subsequent stages (Lara-Astiaso et al, 2014). Recent studies of enforced ESC programming to motor neurons also revealed dynamic multi-step chromatin remodeling (Rhee et al, 2016; Velasco et al, 2016). It should be noted, though, that conventional Yamanaka-factor iPSC reprogramming is a slow and stochastic process (Buganim et al, 2012; Hanna et al, 2009; Smith et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Mechanistically, the molecular hand-off between Pou3f1 and Atoh1 may be mediated at the level of transcriptional regulation. Namely, analogous to the regulatory model that governs mouse motor neuron differentiation proposed by Rhee et al (2016), we suspect that, as cells leave the RL, the enhancer driving Atoh1 expression at the RL is transcriptionally silenced. This silencing event frees up a yet to be identified transcription factor, now able to bind to another enhancer that drives the expression of Pou3f1 along the SS.…”
Section: A Molecular Hand-off Between Pou3f1 and Atoh1 During Glutamamentioning
confidence: 81%